AI Literacy, Digital Self-Efficacy, and Learning Resilience as Predictors of Academic Success Across Urban and Rural Students - Dewi, Erni Ratna; Alam, Andi Aminullah (Journal of Educational Science and Technology (EST), 2025)
The COVID-19 pandemic accelerated the adoption of AI-driven learning technologies in Indonesia, yet digital disparities particularly between urban and rural students persist. While prior studies have explored AI literacy, self-efficacy, or resilience separately, little is known about how these psychological and digital competencies interact to support academic success across diverse socio-geographic settings in Indonesia. This study investigates how AI literacy and digital self-efficacy influence academic performance, with learning resilience as a mediator and school location as a moderator. A quantitative, cross-sectional survey was conducted with 452 university students selected through convenience sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA). Results show that AI literacy (β = 0.33, p < 0.05) and digital self-efficacy (β = 0.41, p < 0.01) significantly enhance learning resilience, which in turn predicts academic performance (β = 0.35, p < 0.01). Mediation was confirmed via bootstrapping, indicating that learning resilience fully mediates the effect of both predictors on GPA. MGA results show that these effects are significantly stronger among urban students. The findings highlight the need to strengthen psychological and digital capacities, especially in rural settings. By linking student adaptability to academic success, this study directly supports the Merdeka Belajar policy’s emphasis on differentiated, technology-supported learning and reinforces the urgency of targeted interventions for equitable education in the AI era.